Tourism and the Problem of Tick-Borne Infections in the Republic of Buryatia - G. A. Danchinova; A. V. Lyapunov; M. A. Khasnatinov (Эпидемиология и вакцинопрофилактика)
For the first time the current situation with tick-borne infections in recreational places of the Republic of Buryatia is evaluated. According to the data of the Center for diagnostic and prophylaxis of tick-borne infections (Irkutsk) collected in 2007 - 2014 the tick-borne encephalitis, Lyme disease, monocytic ehrlichiosis and granulocytic anaplasmosis are widely spread in most popular recreational places of south coast of the Baikal Lake and Tunka valley.